Pengaruh Daya Tarik Rasional Iklan Dan Daya Tarik Emosional Iklan Spotify Premium Terhadap Keputusan Berlangganan Pelajar Generasi Z Di Kota Bandung - Maharani Mustika Putri Parijin (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The rapid development of technology today has brought the internet to facilitate various aspects of human life. One of the basic human needs that is most helped by the presence of the internet is communication and entertainment. Using digital media to fill time and seek entertainment, such as listening to music with the Spotify application, is increasingly popular with the younger generation. Social media, which is a platform for communicating, is currently considered a marketing opportunity to reach a wider and more precise target audience. This study aims to identify and explain the effect of advertising appeal which can be categorized into two types, namely rational appeal and emotional appeal of advertising on the decision to subscribe to Spotify Premium in 108 sample student respondents in the city of Bandung. Through multiple linear regression analysis with data processing on SPSS version 29, this study shows the results of the partial influence of the rational appeal of advertising has an effect of 27% and the emotional appeal of advertising has an effect of 54.2% on purchasing decisions. Meanwhile, the simultaneous effect of the two ad appeals is 69.3% on purchasing decision.